2013
DOI: 10.1007/s11356-013-1877-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of zeolites for radium removal from mine water

Abstract: For removal of radium from saline waters in Upper Silesian mines, several methods of purification have been developed. The most efficient one is based on application of barium chloride, which was implemented in full technical scale in two Polish coal mines several years ago. Very good results of purification have been achieved—the removal efficiency exceeding 95 % of the initial activity. Another possibility for the removal of different ions from salty waters and brines is the application of zeolites. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 19 publications
0
37
0
3
Order By: Relevance
“…61 %) and has approximately six times higher the specific BET surface area than the fly ash from which it has been synthesized. These properties indicate a possibility to use the Na-P1 zeolite as an adsorbent for many pollutants, including heavy metals (Wang et al 2009), radionuclides (Chałupnik et al 2013), or gases such as CO 2 (Walton et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…61 %) and has approximately six times higher the specific BET surface area than the fly ash from which it has been synthesized. These properties indicate a possibility to use the Na-P1 zeolite as an adsorbent for many pollutants, including heavy metals (Wang et al 2009), radionuclides (Chałupnik et al 2013), or gases such as CO 2 (Walton et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…desulfurization of fuel (Muzic et al 2012) or oil refining (Zhu et al 2013)], and environment engineering [i.e. to remove of ammonium ions (Franus and Wdowin 2010;Liu et al 2012) or heavy metals from waters and waste water (Merrikhpour and Jalali 2013;Wang et al 2009) or separation/adsorption of gases such as CO 2 (Walton et al 2006;Wdowin et al 2012), SO 2 (Yi et al 2012) or mercury (Morency et al 2002), and removal of radionuclides from the mine waters (Chałupnik et al 2013)]. …”
Section: Introductionmentioning
confidence: 99%
“…They are classified by their pore size, which ranges from 0.5 to 1.2 nm, for the adsorption of gas molecules [67]. They also have been widely applied to gas separation and purification [68][69][70].…”
Section: Zeolitesmentioning
confidence: 99%
“…However, more interesting is its future possible application, as an adsorbent for various pollutants (including radioactive elements and heavy metals). It has been demonstrated that, manufacture of synthetic zeolites from CFA is a relatively straightforward procedure [18][19][20][21][22] and such materials have been found to be effective in the removal of various pollutants from different environments (water, soils, flue gases) [15,[23][24][25][26][27][28][29]. A comparison with natural zeolites shows that synthetic zeolites are better for the removal of mercury compounds, due to the consistent size of the channels and chambers, in contrast to the microstructure of natural zeolites sizes which can be variable and often associated with a number of lattice defects [30].…”
Section: Introductionmentioning
confidence: 99%